Cave systems in Phong Nha - Ke Bang area - Nguyen, Hieu (ĐHQGHN, 2017)
After 22 years with 13 collaborative research expeditions between the Faculty of Geography, VNU University o f Science, and the BCRA, many eaves in the great limeston eblocks o f Phong Nha Ke Bang have been explored and surveyed with a total length of 163 km. Most of them are river caves, connected together to form three main systems: Phong Nha cave system, Hang Vom system and Nuoc Moc system. Phong Nha cave system starts from Hang Khe Ry - the world’s longest river cave, to Hang Thung, En, Tra Anh and finally, Phong Nha cave, with a total length o f 79.1km. Hang Vom system starts from Rue Ca Roong cave and ends with Hang Vom with a total length o f 44.3km . Nuoc Moc system which has a large basin located in the west o f Chay River flowing through caves Vuc Ky, Nuoc Lan and Ha Lau is 14.1km long. Most recently, Son Doong Cave o f the Phong Nha system was discovered and is the world’s largest cave passage. Some caves have been developed for tourism activities such as Phong Nha Cave and Paradise Cave more recently. However, tourism activities have a large effect on the caves. Beside the research results o f the cave systems in Phong Nha Ke Bang, this report will provide the following analyses: evaluation o f the impact o f tourist activities and environmental changes in the caves, and propose solutions for the effectivemanagement and sustainable development o f this valuable resource.